The POLITICS of ISLAMIC MALAY of RAJA ALI HAJI - Faishal Shadik (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
This paper studies political model developed by Raja Ali Haji. In his thought on politics, the government should be in the form of kingdom which its authority is held by a king to implement the prosperity of the society. It means that a government needed by Raja Ali Haji is a kingdom based on Islam. This indicates that, based on political science, this kind of government could be classified as ‘Theo-monarchy’, a kingdom government based on God law, i.e. Islamic law. God law used as a foundation for governmental processes will be able to limit destructive characteristics of a king. In fact, a king should have big responsibility to manage his task as a state leader, namely to bring his people to be happy or prosperous both in the world and here after.